Integrated Interaction between Tourism, Economy, and Ecology in Indonesia: Coupling Coordination Degree Method - Faizah, Raudlatul; Kusumawardani, Deni (Faculty of Economics and Business Universitas Jenderal Soedirman, 2024)
Indonesian tourism sector becomes an important part of national development planning over the past decade. However, the development of the tourism sector stimulates many negative ecological issues. Tourism has a complex relationship with the economy and ecological quality. it is essential to investigate progress of tourism-economy-ecology system. An integrated study of this system can be analyzed using coupling coordination degree method (CCDM) that provides overview of interaction and level of coordination in systems. The findings show that coupling degree between tourism-economy-ecology systems increases from run-in to high-phases. This condition indicates that there was strong connection between systems during observation. Meanwhile, the coupling coordination degree constitutes an ever-increasing evolution from approaching-disorder to well coordination. It shows that the systems are increasingly supportive of each other. Conversely, higher level of coordination is accompanied by decline in environmental system. Promoting ecological quality becomes critical policy for sustainable tourism growth.